2009
DOI: 10.1590/s0124-00642009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Niveles de excreción urinaria de yodo en escolares del Quindío, 2006-2007

Abstract: The population being studied had severe iodine deficiencies (rural) and excessive intake (urban population), suggesting the absence or poor control of an iodization programme and additional exposure to factors causing iodine disorders. A programme is required for monitoring iodine disorders in the school population being studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
3
2
11
Order By: Relevance
“…In a study in which 444 urinary samples were obtained from school age children in the central and rural regions of Armenia, Tebaida and Caimo, no significant difference could be found between the girls and boys (24). In this study, iodine deficiency was found with a rate of 11% and 18%, respectively.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In a study in which 444 urinary samples were obtained from school age children in the central and rural regions of Armenia, Tebaida and Caimo, no significant difference could be found between the girls and boys (24). In this study, iodine deficiency was found with a rate of 11% and 18%, respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, iodine deficiency was found with a rate of 11% and 18%, respectively. In this iodine deficiency study, it was shown that iodine deficiency was found with a significantly higher rate in individuals with poor economical level (24). Similarly, no difference related with gender was found in terms of iodine deficiency in our study and iodine deficiency was observed with a higher rate in the rural region where the economical level was lower.…”
Section: Discussioncontrasting
confidence: 45%
“…In 2003, the National Agency for Sanitary Surveillance (ANVISA in the Portuguese acronym) established a norm for iodine concentration of 20-60 mg/kg in kitchen salt. In South America, iodine nutritional status improved considerably, with excessive iodine intake currently occurring in countries like Brazil, Chile and Colombia [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(1) y similares a los escolares brasileños (14) , argentinos (15 y colombianos (16) . La mediana de yoduria en el área rural estuvo dentro de los niveles considerados adecuados por la OMS, mientras que la mediana de yoduria en el área urbana estuvo por encima de los niveles recomendados por la OMS.…”
Section: Discussionunclassified